PEMIKIRAN HASAN AL-BANNA ; ANALISIS TENTANG PENDIDIKAN KARAKTER - Mardiana; Alfin Nurofikoh; Chanifudin (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
Character education is an important aspect in the formation of the personality of individuals with noble character. In the context of Islamic education, figures such as Hasan Al-Banna have a significant contribution in offering character education concepts relevant to Islamic values. This study aims to explore the relevance of Hasan Al-Banna's character education in the perspective of Islamic education. Using qualitative approaches and literature studies, this study analyzes the thoughts and concepts of Hasan Al-Banna's character education and relates them to the challenges and needs of character education. The results showed that the concept of Hasan Al-Banna's character education, which is based on Islamic principles, is still very relevant and provides a holistic solution in overcoming moral degradation. This research contributes to the development of insights and strategies for Islamic character education that are contextual and adaptive to the times.